Investigation of track settlement and ballast degradation in the high-speed railway using a full-scale laboratory test. (September 2019) - Zhang, Xu; Zhao, Chunfa; Zhai, Wanming; Shi, Can; Feng, Yang
This paper presents a full-scale laboratory test for investigating the track settlement and ballast degradation of the ballasted track–subgrade system on the high-speed railways. The test was carried out on a full-scale test platform with a ballasted track–subgrade system constructed exactly according to the construction standards of high-speed railways in China. In this test, four million cycles of cyclic loads simulating repeated high-speed train loads with an axle load of 140 kN were applied to the ballasted track–subgrade system through a specialized loading system. The vertical displacement and settlement of the rail, the sleepers and the subgrade at various sections and depths were recorded during the test. The test results show that the settlement of the high-speed railway ballasted track is very less. A logarithmic model was proposed for predicting the settlement of the high-speed railway ballasted track by fitting the measured data. Moreover, some painted ballast samples were embedded into the tested track to investigate the ballast degradation. After the test, it was found that more than 80% of the painted ballast grains remained intact and less than 20% were degraded. Four different ballast degradation phenomena were observed: corner or edge breakage, surface scratch, surface crack and the production of fine particles. The test results indicate that the high-speed railway ballasted tracks in China are very stable and the settlement is less under long-term cyclic loads, which could significantly benefit the track geometry and the railway maintenance work.